Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1038/sj.mp.4001140
|View full text |Cite
|
Sign up to set email alerts
|

The −2 bp deletion in exon 6 of the ‘alpha 7-like’ nicotinic receptor subunit gene is a risk factor for the P50 sensory gating deficit

Abstract: Abnormality in the P50 auditory-evoked potential gating is an endophenotype associated with schizophrenia. Biochemical and genetic studies have suggested that the alpha 7 nicotinic acetylcholine receptor (nAChR) is involved in this sensory gating deficit. Two related alpha 7 genes (CHRNA7 and CHRNA7-like gene) resulting from a partial duplication (from exon 5 to exon 10) are present in the human genome. Two types of genetic variation, a large deletion and a −2 base-pair deletion in exon 6 resulting in a trunca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 12 publications
4
62
1
Order By: Relevance
“…Of the six previous studies involving CHRFAM7A variants and either a psychosis phenotype or endophenotype, 19,[21][22][23][24]67 four found a significant association with the 2-bp deletion. However, there is no consistency with the phenotype involved.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Of the six previous studies involving CHRFAM7A variants and either a psychosis phenotype or endophenotype, 19,[21][22][23][24]67 four found a significant association with the 2-bp deletion. However, there is no consistency with the phenotype involved.…”
Section: Discussionmentioning
confidence: 83%
“…We found no association of the 2-bp deletion with schizophrenia in the above study, but an association with schizophrenia has since been reported. 21 Other studies have found that the 2-bp deletion is associated with bipolar disorder, 22 P50 sensory gating deficit 23 and deficits in episodic memory, 24 another endophenotype proposed for schizophrenia. Recent genome-wide scans for CNVs showed that much rarer CNVs at 15q13.3, usually involving deletion of B2 Mb from CHRFAM7A to CHRNA7, are overrepresented in many neurological and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Electroencephalographic activity was recorded as described previously, 5,11 and according to the P50 suppression paradigm. 12,13.…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…4 In a previous work, we have shown that the presence of at least one À2 bp deletion located in exon 6 of the CHRNA7-like gene is a risk factor for P50 abnormality in the general population. 5 Recently, Leonard et al 6 identified several polymorphisms in a core promoter region of the CHRNA7 gene. They showed that most of these variations result in a decreased transcription by using the luciferase reporter gene assay, and they reported a significantly greater prevalence of functional promoter variants in subjects who had an inhibitory deficit.…”
mentioning
confidence: 99%
“…Smoking affects sensory gating. Several studies have shown that promoter variants (in the a7 gene) or variants located in the a7-like gene are associated with P50 inhibition deficits (Raux et al 2002; for review, see Leonard and Freedman 2006). This paradigm has also been used to identify a potential susceptibility locus for schizophrenia on chromosome 15, a region where the gene for the a7 nicotinic receptor is located.…”
mentioning
confidence: 99%